ISOLATION OF CYANIDE DEGRADING BACTERIA FROM GOLD-MINE TAILING - Mohamad Yani dan Dwi Meity Handayani (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTThe isolation and identification of cyanide degrading  bacteria conducted from the gold-mine tailing impoundment. The fresh tailing contained 0.81 – 2.17 ppm of CN and  cyanide degrading  bacteria populations.  From fresh tailing sample, the cyanide degrading  bacteria had been enriched using cyanide media which composed of 200 ppm of CN, 1-8 g/L of nutrient broth and trace element.  By several times in enrichment culture, isolation and selection of single colonies which were formed on nutrient agar plates, several cyanide degrading  bacteria were isolated successfully.  Those bacteria were simplify identified by morphological and biochemical tests as Thiobacillus sp.  The characteristics of Thiobacillus sp. were  facultative anaerobic, rod shaped, motile, Gram negative,  neutrophilic, and mesophilic.  Thiobacillus  B31P123  and B33P123  could utilize cyanide up to 500 ppm as its sole source of energy for growth.  During the degradation of cyanide, ammonia was produced as the final products which slightly increased the pH of the medium   Both isolates (B31P123 and B33P123) oxidized 200 ppm of CN which performed at rate of 0.32 and 0.35 ppm of CN/hr during logarithmic phase and produced ammonium up to 50 and 46 ppm, respectively.  The nitrogen product was utilized at more than 80% for biomass cells growth.Keywords:  cyanide, gold-mine-tailing, isolation, Thiobacillus